IMPLEMENTASI APLIKASI ZAHIR UNTUK MENENTUKAN ANALISA RASIO KEUANGAN - Fahrizal, Muhamad Fani; Masripah, Siti (LPPM Universitas Nusa Mandiri, 2018)
Zahir as one of the accounting software that has the ability in terms of processing financial data, starting from the process of selling goods, purchasing goods, setting up inventory to making reports needed by the company. The benefits that can be obtained are, companies can find out about the company's financial position, decision making and technically can minimize errors. The results obtained from the use of Zahir Accounting as a substitute for manual recording systems can be observed in terms of financial statements and financial report analysis produced between manual recording and Zahir Accounting showing the same results. The results of the application of zahir application on corporate finance for Ratio Analysis can be obtained as follows: profitability ratio shows results where 5.29% for Return On Equity, 19.13% for Gross Margin, 8.64% for Net Margin, and 91, 36% for Operating Ratio. This number is to determine the ability to carry out its obligations as a company.